The Development of an Oolong Tea Lumps Sorting Machine with Suitable Technology Suitable for the Community - Bhudtiyatanee, Matas; Mahawan, Taweesak; Wannaphrom, Wathanyu; Buamasung, Bantita; Ounjaijom, Thawatchai (RMUTL Journal of Socially Engaged Scholarship, 2023)
TThe aim of this research was to develop suitable technology for sorting oolong tea lumps for the Royal Project Foundation’s processing and product development factory (Mae Hia) in 2022. The oolong tea lump sorting machine consisted of a conical tank to fill and concentrate the lumps of tea, 4 layers tray of a sieve set. The tray was a circular shape hole in 3 layers with a diameter of 10, 8, and 2 mm and an empty tray without holes on the bottom layer. The tray was attached to the machine frame at an angle of 4 and 8 degrees at sorting speeds of 165, 185, and 213 rpm. The results of the experimental operation of the oolong tea lump sorting machine showed that at an inclination angle of 4 degrees, the drive shaft speed of 213 rpm had the highest proportion of the average mass of the oolong tea lump that could be sorted at 99.47% and the least attached to the tray when accounting for 0.53%, respectively. The Royal Project Foundation's processing and product development factory (Mae Hia) can use the tea lumps sorting technology from their operation to enhance the potential of traditional tea lumps sorting.